EFEKTIVITAS TERAPI RENDAM KAKI AIR HANGAT TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI SEBAGAI PENERAPAN HOLISTIC CARE: A LITERATURE REVIEW (Al-Asalmiya Nursing: Jurnal Ilmu Keperawatan (Journal of Nursing Sciences), 2024)
Hydrotherapy is a vital naturopathic treatment modality that utilizes water. Beyond its ability to reduce high blood pressure, hydrotherapy offers numerous benefits, including alleviating muscle stiffness, soothing injured muscles, enhancing the immune system, and providing detoxification effects, as well as improving skin health. Through the application of warm water, hydrotherapy naturally aids in stabilizing and lowering blood pressure. This study aims to assess the effectiveness of warm foot soak therapy in reducing blood pressure among hypertensive patients. Literature review focusing on the intervention of warm foot soak therapy in lowering blood pressure. The articles for this literature review were selected through a search using keywords such as Hypertension, Hydrotherapy, and Blood Pressure on databases including Science Direct, Pubmed, Ebsco, and Google Scholar. This literature review study significantly concluded that warm water foot soak therapy can reduce blood pressure in patients with hypertension. Warm foot soak hydrotherapy is an evidence-based practice that is effective in improving holistic patient care, offering a safe and effective non-pharmacological alternative for managing high blood pressure. Therefore, hydrotherapy is worth considering as part of standard care for individuals with high blood pressur.
Keywords: Hidroterapi; Hipertensi; Terapi Rendam Kaki.